Avaliação do desempenho dos métodos de proteção contra a perda de excitação em geradores síncronos: uma contribuição para a melhoria da técnica baseada em combinações de sinais - Gallas, Mairon (2019)
This work aims to evaluate the behavior of synchronous generators against total (TLOE) and partial (PLOE) loss of excitation, to demonstrate the behavior of the main electrical variables involved, to analyze the performance, propose modifications and to perform a comparative study among the several LOE protection methodologies proposed in the literature. The methods are presented in order to provide the main variables to be parameterized according with the protection technique, in order to facilitate the use of these by professionals in the area, besides helping to identify the circumstances in which a method is more appropriate than the other. In order to identify the performance of each technique, computational simulations of LOE are performed, with the excitation voltage being reduced to 100%, 80% and 60% of the steady state excitation voltage. Also in this context, trying to understand the influence of the FACTS controllers of the type STATCOM, simulations are realized with this equipment. As the methods have adjustments that are based on the parameters of the protected generator, tests were performed on two different systems with different machines at different operational points. In this way, it was possible to conclude that the methods do not behave in the same way for generators of different sizes and in different systems, it is still possible to conclude that the methods currently used commercially have difficulty of acting against PLOE and end up suffering influence of the STATCOM device in its performance, delaying the trip of the protection or, often, sub-reaching the protection zones. Since the method proposed by Mahamedi, Zhu e Hashemi (2015) has a good performance against TLOE, it is recommended to use this in order to guarantee the reliability and efficiency of the protection against TLOE, mainly because it is a method of easy parameterization and have as a characteristic do not vary their behavior according to the nominal power of the generator. Also, it is recommended to use the technique proposed by Amini, Davarpanah e Sanaye-Pasand (2015) with the modifications proposed in this dissertation, as this method proved to be the best for PLOE detection.